Water Use for Drip-Irrigated Watermelon with Plastic Mulch in Florida - Sanjay Shukla; Niroj K. Shrestha; Thomas A. Obreza; Brian J. Boman (EDIS)
Watermelon is an important crop in Florida and accounts for a significant part of its agricultural water use. Watermelon is grown in open fields and on raised plastic-mulched beds, with the latter being the predominant production system in Florida. Accurate water use estimates for this crop are needed to develop better water allocation and management plans as well as for irrigation management. This publication summarizes the results from a crop water-use study for the drip-irrigated watermelon in south Florida. This 3-page fact sheet was written by Sanjay Shukla, Niroj K. Shrestha, Thomas A. Obreza, and Brian J. Boman, and published by the UF Department of Agricultural and Biological Engineering, August 2014.